Dehydration, Water Fluxes, and Permeability of Tobacco Leaf Tissue - Graziani, Y. (1971)
Removal of the lower epidermis from a tobacco leaf allows a faster and wider range of water fluxes, without damaging the mesophyll. It also permits a more direct examination of the photosynthetic potential of the tissue at various levels of hydration. The rehydration rate of leaf discs is essentially linear. It decreases with leaf age and is correlated with the rate of dehydration, but it is independent of the tissue's water potential, as estimated by the isopiestic method. The hydraulic permeability coefficient of water influx is directly related to water potential of the tissue, suggesting a mechanism for the regulaton of the hydration level of the leaf tissue. The “energy of activation” of rehydration amounts to about 9 kilocalories per mole at intermediate dehydration, but it greatly declines following water loss in excess of 600 milligrams per gram fresh weight. The excessive dehydration is also characterized by a major increase in permeability (monitored by efflux of ions and materials absorbing ultraviolet light) and by a parallel decrease in photosynthetic activity. The interrelationship of these effects of excessive dehydration is discussed.